The importance of applying the asset valuation model to medium-sized enterprises - Zimonjić Marijana (Ekonomija: teorija i praksa, 2025)
The study presents the importance of realistic asset valuation in medium-sized enterprises, which fundamentally requires the assessment of assets at fair value using valuation techniques as of the date of the appraisal. The aim of the paper is to highlight the importance of valuing company assets based on so-called fair value, which is entered into the company's year-end financial statements once per year. Such an approach forms the basis for a practical representation of the actual state of asset values, which in turn underpins sound managerial decision-making in the operations of medium-sized enterprises. Presenting accurate financial reports in this way is essential for reflecting the real business performance of companies in the Republic of Serbia. The results obtained show a significant deviation in asset valuation before and after the new fair value-based appraisal. Additionally, the study highlights differences in the valuation of construction facilities, transportation assets, and equipment before and after the fair revaluation. Only in the case of transportation assets and equipment related to workshop operations was a slightly weaker effect observed compared to other factors. The study has practical applicability across a wide range of companies and was conducted by comparing asset values before and after revaluation, particularly in the context of preparing year-end financial statements for enterprises in the Republic of Serbia.